The Pathophysiology of Pleural Effusions - Sahn, Steven A. (Annual Review of Medicine, 1990)
Two features of human parietal pleura explain its role in the formation and removal of pleural liquid and protein in the normal state: the proximity of the microvessels to the pleural surface and the presence of stomata situated between mesothelial cells. For pleural fluid to accumulate in disease, there must be increased production from increased hydrostatic pressure, decreased oncotic or pleural pressure, increased microvascular permeability, or peritoneal-pleural movement. The rate of formation must overwhelm lymphatic clearance, which may be decreased by hydrostatic forces or blocked by malignant infiltration.
Keywords: visceral pleura